Alterations of the transcriptome of Sulfolobus acidocaldarius by exoribonuclease aCPSF2. - Birgit Märtens; Fabian Amman; Salim Manoharadas; Lukas Zeichen; Alvaro Orell; Sonja-Verena Albers; Ivo Hofacker; Udo Bläsi (PLoS ONE)
Recent studies identified a 5´ to 3´ exoribonuclease termed Sso-RNase J in the crenarchaeon Sulfolobus solfataricus (Sso), which has been reclassified to the aCPSF2 (archaeal cleavage and polyadenylation specificity factor 2) group of β-CASP proteins. In this study, the Sso-aCPSF2 orthologue of Sulfolobus acidocaldarius (Saci-aCPSF2) was functionally characterized. Like Sso-aCPSF2, Saci-aCPSF2 degrades RNA with 5´ to 3´ directionality in vitro. To address the biological significance of Saci-aCPSF2, a deletion mutant was constructed, and the influence of Saci-aCPSF2 on the transcriptome profile was assessed employing high throughput RNA sequencing. This analysis revealed 560 genes with differential transcript abundance, suggesting a considerable role of this enzyme in RNA metabolism. In addition, bioinformatic analyses revealed several transcripts that are preferentially degraded at the 5´ end. This was exemplarily verified for two transcripts by Northern-blot analyses, showing for the first time that aCPSF2 proteins play a role in 5' to 3' directional mRNA decay in the crenarchaeal clade of Archaea.